A new species of pink-flowered Leptocereus (Cactaceae) from Cuba - Barrios, Duniel; Majure, Lucas C. (Phytotaxa, 2025)
A new species of Leptocereus (Cactaceae) from Cuba is described and illustrated. We compare Leptocereus gonzaleztorresii sp. nov. based on morphological and anatomical data with other cacti of the Cuban subclade of pink-flowered Leptocereus (L. leonii, L. scopulophilus, L. wrightii), to which it belongs. Twenty-one vegetative and reproductive characters were analyzed through canonical discriminant and classificatory analyses to evaluate the separation between species. Leptocereus gonzaleztorresii is characterized by flowers with external stamens with aborted anthers, and brown fruits. Classificatory analyses correctly classified 100 % of the individuals of L. gonzaleztorresii. We provide an identification key to the Cuban subclade of the pink-flowered Leptocereus.